Recent Acceleration of a Rock Glacier Complex, Ádjet, Norway, Documented by 62 Years of Remote Sensing Observations. Issue 16 (23rd August 2018) - Eriksen, H. Ø.; Rouyet, L.; Lauknes, T. R.; Berthling, I.; Isaksen, K.; Hindberg, H.; Larsen, Y.; Corner, G. D.
Abstract: Recent acceleration of rock glaciers is well recognized in the European Alps, but similar behavior is hardly documented elsewhere. Also, the controlling factors are not fully understood. Here we provide evidence for acceleration of a rock glacier complex in northern Norway, from 62 years of remote sensing data. Average annual horizontal velocity measured by aerial feature tracking increased from 0.5 myr −1 (1954–1977) to 3.6 myr −1 (2006–2014). Measured by satellite synthetic aperture radar offset‐tracking, averages increased from 4.9 to 9.8 myr −1 (2009–2016) and maximum velocities from 12 to 69 myr −1 . Kinematic analysis reveals different spatial‐temporal trends in the upper and the lower parts of the rock glacier complex, suggesting progressive detachment of the faster front. We suggest that permafrost warming, topographic controls, and increased water access to deeper permafrost layers and internal shear zones can explain the kinematic behavior. Plain Language Summary: Using remote sensing data we document unusual high surface displacement and accelerations on a rock glacier complex in a mountain hillside in northern Norway. Increasing creep rates have been reported from the European Alps, but an acceleration of this order has not been documented in Scandinavia before. Rock glaciers are permafrost landforms consisting of a mix of ice and debris. Using aerial photos, we document an acceleration from 0.5 m per year (1954–1977) to 3.6 m per year (2006–2014) for the lower parts of the rock glacier complex. For the same area, we observe an increase from 4.9 to 9.8 m per year, measured by satellite‐based radar between 2009 and 2016. Maximum velocities increased from 12 to 69 m per year. Results suggest that the fast lower part is detaching from the slower upper part. Radar data delineate areas with subsidence and uplift, compression, and extension. Increase in temperature and precipitation during the 62‐year period indicates possible permafrost degradation. Our work demonstrates the value of combining remote sensing data sources in documenting permafrost landforms in the Arctic. Important work still remains to document and understand their evolution and the effects of climate change. Key Points: Sixty‐two years (1954–2016) of aerial photography and radar data document recent acceleration of a rock glacier complex in northern Norway Results show spatial and temporal variations as extension and compression, uplift, and subsidence in a permafrost landform Simultaneous increase of temperature and precipitation suggests that the landform is affected by permafrost warming